واقع الثقافة الاسلامية في ماليزيا : دراسة تحليلية بحث مقدم لنيل درجة الماجستير في تخصص الثقافة الاسلامية - ابن عبد اللطيف، محمد نور الحفيظ; Umm Al-Qura University . x (2020)
In the name of Allah, Most Gracious, Most Merciful. Praise be to Allah the lord of the world and peace be upon the honoured prophet Muhammad SAW the messenger and to all his families and companions. This thesis is proposed with the aim to describe in details Islamic cultures in Malaysia. This paper will include the factors that stimulating the Islamic culture in Malaysia; several challenges since then until now; and the solutions for these challenges. To meet those objectives, this thesis is divided into; Introduction; which will explains the purpose of this thesis regarding the reality of Islamic cultures in Malaysia and thoroughly explain on Malaysian nation. The first chapter is presented on the Tributaries to Islamic Cultures (Rawafid Thaqafah Islamiyah) in Malaysia which comprises of six elements; family guidance, function of mosque, government and private school, Islamic organizations and the role of media in spreading the Islamic culture in Malaysia and also the effect it takes on the society. The second chapter is entitled 'The Challenges of Islamic Culture in Malaysia'. It is divided into four areas. The first is compromised thinking affected by either secularism, globalization, liberalism or capitalism. The second area is different sects including Christianity, shie', sufism, heresy etc. The third area is the effect of modernization. The third chapter of this thesis will explain the measures to overcome the problems and challenges mentioned.
Thesis (Degree of Master) - Umm Al-Qura University, 2016
Includes bibliographical references (leaves 553-562) and index
Keywords: Umm Al-Qura University -- Dissertations; Umm Al-Qura University -- x -- Dissertations; Dissertations, Academic; Islamic civilization